1986
DOI: 10.1093/oxfordjournals.aje.a114408
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms in Relation to Physical Health and Functioning in the Elderly

Abstract: The associations between depressive symptoms and functional disability and chronic conditions are examined in an elderly cohort of 2,806 noninstitutionalized men and women living in New Haven, Connecticut who were interviewed in 1982 as a part of the Yale Health and Aging Project. The aim is to explore several potential sources of invalidity in using the Center for Epidemiologic Studies-Depression scale (CES-D) to measure depressive symptoms in elderly populations. In particular, the authors are concerned with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
451
7
11

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 769 publications
(514 citation statements)
references
References 24 publications
45
451
7
11
Order By: Relevance
“…Physical illness has long been recognized to be one of the most important risk factors for depression in older adults (Berkman et al 1986 ;Kennedy et al 1989 ;Prince et al 1997). Indeed, this dominant role of physical illness may be one of the most significant differences between late-life depression and depression in younger adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical illness has long been recognized to be one of the most important risk factors for depression in older adults (Berkman et al 1986 ;Kennedy et al 1989 ;Prince et al 1997). Indeed, this dominant role of physical illness may be one of the most significant differences between late-life depression and depression in younger adults.…”
Section: Discussionmentioning
confidence: 99%
“…The total CES-D score ranges from 0 to 60. A score of 16 has generally been used as indicative for clinically relevant depressive syndromes (Berkman et al 1986). The psychometric properties of the scale were found to be good in older populations (Radloff & Teri, 1986 ;Beekman et al 1994), and in a number of studies the overlap with symptoms of physical illness has been shown to be limited (Berkman et al 1986 ;Foelker & Schewchuk, 1992).…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it seems likely that self-reported effects of job on health are measuring a slightly different construct than job satisfaction. relationship between physical and mental health (Cohen & Rodriguez, 1995;Patrick & Erickson, 1993;Ryff & Singer, 1998;Salovey, Rothman, Detweiler, & Steward, 2000), with longitudinal studies finding that mental health predicts subsequent physical health outcomes (Fiscella & Franks, 1997;Levanthal, Hansell, Diefenbach, Leventhal, & Glass, 1996;Penninx et al, 1998) and physical illness predicts psychological well-being (Berkman et al, 1986;Wickrama, Lorenz, Conger, Matthews, & Elder, 1997). Thus, the effects of work on mental and physical health are also likely to be inextricably linked.…”
Section: Dependent Variablementioning
confidence: 99%
“…This article deemphasizes the mathematical theory of loop analysis published elsewhere (Levins, 1974;Puccia and Levins, 1986;Dambacher, et al, 2002;Justus, 2005), and instead guides readers into its application and interpretation. This research is informed by results of an unpublished analysis (manuscript, Dinno, et al) of observed depressive symptomatology over a course of 13 years in a population of 2812 individuals aged 65 and older in New Haven, Connecticut, (Berkman et al, 1986) which were related to spatially detailed representations of building vacancy produced by the annual New Haven Fire Department vacant building census and the New Haven City Plan's GIS database of real property. Neighborhood vacancy was found to strongly explain variation in depressive symptom scores, after controlling for individual factors including economic impoverishment and individual proximity to vacant buildings.…”
Section: Introductionmentioning
confidence: 99%